A New Approach on the Complex Diffusion Tensor in the Ionospheric F-region with Low Latitudes - Yasar, Mehmet; Kurt, Kadri; Yesil, Ali (Pleiades Publishing Ltd, 2025)
Taking into account the real magnetic field geometry of Earth in the northern hemisphere, this work produced the equations of real diffusion coefficients for the ionospheric F region (390, 410, 450, 500, 550, 600 km) at low latitudes. In a steady state, diffusion coefficients show real values, while in an unstable state, they show complex values with real and imaginary components. We performed numerical calculations at F region altitudes within the ionospheric plasma to determine the diffusion coefficients for both cases. The results show that in the steady state, the diffusion coefficients have values that are very close to the speed of light. In unstable conditions, on the other hand, the real parts are generally close to the conductivity values, while the imaginary parts are similar to the sound speed magnitudes. The fundamental focus of this technique is to demonstrate and calculate the complex structure of diffusion coefficients in the ionosphere, representing the first such instance in the literature.
Keywords: ionospheric plasma; complex diffusion coefficients; ionospheric F region; magnetic field